Odpowiedzi

Najlepsza Odpowiedź!
2010-02-22T23:17:08+01:00
A) 9x-1=7x-8
9x-7x=-8+1
2x=-7
x=-3,5
b)2(3x-1)=-2(-2x-4)
6x-2=4x+8
2x=10
x=5
c)
5x-(2x-1)=x+(5-x)
5x-2x+1=x+5-x
3x=4
x=1⅓

  • Użytkownik Zadane
2010-02-22T23:20:18+01:00
A) 9x+7x=1-8
13x=-7 /:13
x=-7/13
b) 6x-2=4x+8
6x-4x=2+8
2x=10 /:2
x=5
c) 5x-x=x+4x
4x=5x /:4
x=5/4
chyba tak :P
2010-02-22T23:26:55+01:00
A)9x-1=7x-8
9x-7x=-8+1
2x=-7/:2
x=-3,5

b)
2(3x-1)=-2(-2x-4)
6x-2=4x+8
6x-4x=8+2
2x=10/:2
x=5

c)

5x-(2x-1)=x+(5-x)
5x-2x+1=x+5-x
3x=4
x=1,3